Student Organizations and Their Contribution to Quality Assurance and Enhancement in Higher Education Institutions – Case Study: Romania - Andreea Mirică (Revista Română de Statistică, 2014)
The purpose of this paper is to analyze the involvement of student organizations toward quality assurance and enhancement in higher education institutions in Romania. In order to achieve this purpose, a survey among student organizations from the main university cities in Romania has been conducted between December 2013 and May 2014. In order to analyze the results we used the frequency distribution method. One of the main findings of this paper is that there is a strong desire of a high quality education among student organizations, yet some of them do not become involved in activities contributing to quality assurance and enhancement. This paper can become a valuable tool for policy makers of the Romanian national students federations in order to design the best policies meant to encourage all the organizations participate in the quality assurance and enhancement process.